Using WinRhizo® to study and quantify the roots of the oil palm (Elaeis guineensis Jacq.). - Gutiérrez-Soto, Marco V. (2014)
The objective of this work is to introduce the use of WinRhizo® for the quantitative analysis from the root system of crops in general and of the oil palm in particular. The most important morphological, topological and physiological characteristics of roots relevant to agronomic practices are mentioned, as well as the contribution of specialized software packages available for this analysis. Information on the topology, morphology, diameter, branching and color of roots, among other variables quantified by WinRhizo®, is considered as an important tool for the diagnosis, prevention and treatment of stress, and for the evaluation and assessment of agronomic practices applied to correct and improve root and soil conditions. The procedure for oil palm root processing and quantification using WinRhizo® is described, and the adjustments necessary to quantify the root classes recognized for oil palm are provided.